161k views
0 votes
2 - 2n = 3n + 17 solve n

User TVK
by
5.1k points

2 Answers

4 votes

Answer:

Let's solve your equation step-by-step.

2−2n=3n+17

Step 1: Simplify both sides of the equation.

2−2n=3n+17

2+−2n=3n+17

−2n+2=3n+17

Step 2: Subtract 3n from both sides.

−2n+2−3n=3n+17−3n

−5n+2=17

Step 3: Subtract 2 from both sides.

−5n+2−2=17−2

−5n=15

Step 4: Divide both sides by -5.


(-5n)/(-5)=
(-15)/(-5)

n= -3

User Shadow Wizard
by
4.8k points
4 votes

Answer:

n = -3

Explanation:

2 - 2n = 3n + 17

-2 -2

-2n = 3n + 15

-3n -3n

-5n = 15

-5 -5

n = -3


Hope this helps you!!! :)

User Nicolae Maties
by
5.4k points